Tobacco Use and Intimate Relationships Smokers and Non-Smokers Tell Their Stories - Newman, Ian (Springer International Publishing, 2018)
This book presents a wide variety of insights into the effects of smoking on both smokers and nonsmokers. Based on extensive questionnaire surveys from across the USA, this research explores the complex dynamics of intimate relationships and how they are affected by smoking, especially with regard to honest communication. The volume delves into the battles which take place behind closed doors as both smokers and nonsmokers invoke personal rights and argue their positions. Finally, the authors explore how health policy and public policy can better serve both smokers and nonsmokers, and what the future may hold for the regulation of tobacco use. .